2020
DOI: 10.1016/j.scitotenv.2020.138996
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) as coronavirus disease 2019 (COVID-19) pandemic: A global health emergency

Abstract: • Novel coronavirus, SARS-CoV-2 is responsible for coronavirus disease 2019 (COVID-19). • SARS-CoV-2 has caused for human-tohuman transmission worldwide. • Non-pharmaceutical interventions (NPIs) can reduce the transmission of COVID-19. • COVID-19 is a crisis for massive health hazard, big humanitarian and development. • The use of research-based evidence, global response and solidarity may be helpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
322
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 488 publications
(379 citation statements)
references
References 115 publications
(128 reference statements)
2
322
0
19
Order By: Relevance
“…Therefore, they are considered the most vulnerable individuals to get infected with COVID-19. This was confirmed by earlier studies which showed that mortality of COVID-19 is linked with age: 80% of reported deaths in China were of individuals aged over 65 years old, and up to 15% of the deaths in the US were among adults over 70 years (13,14). Similarly, in another large database study that included data from 17 million patients in the UK, the authors of the study highlighted that patients aged >60 years were at higher risk of hospital mortality due to COVID-19, specifically patients aged >80 HR 12.64 (95% CI 11.19-14.28) (15).…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, they are considered the most vulnerable individuals to get infected with COVID-19. This was confirmed by earlier studies which showed that mortality of COVID-19 is linked with age: 80% of reported deaths in China were of individuals aged over 65 years old, and up to 15% of the deaths in the US were among adults over 70 years (13,14). Similarly, in another large database study that included data from 17 million patients in the UK, the authors of the study highlighted that patients aged >60 years were at higher risk of hospital mortality due to COVID-19, specifically patients aged >80 HR 12.64 (95% CI 11.19-14.28) (15).…”
Section: Discussionsupporting
confidence: 80%
“…The 2019 Coronavirus Disease (COVID-19) caused by the novel beta-coronavirus Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV)-2 has a highly variable course ranging from asymptomatic or paucisymptomatic subsets to severe interstitial pneumonia rapidly evolving into acute respiratory distress syndrome (ARDS) [1,2], which has so far already resulted in the deaths of more than 300,000 people worldwide. The identi cation of risk factors of COVID-19 critical disease remains imperative in order to better allocate medical resources and develop data-driven guidelines for more vulnerable patients.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical symptoms of COVID-19 have been reportedly ranged from mild to severe, ultimately leading to death. The mild symptoms included fever, cough, shortness of breath and pneumonia after viral infection, while the severe cases would rapidly developed to acute respiratory distress syndrome, septic shock, metabolic acidosis, coagulation dysfunction and multiple organ failure that eventually brought about mortality [19,20]. There has been no effective antiviral drug to treat COVID-19 until now, even though signi cant efforts are used to develop therapeutic interventions against coronavirus infection [2].…”
Section: Discussionmentioning
confidence: 99%